Synonymy of Reinholdina deelemanorum Giachino & Moravec, 2009 (Coleoptera: Leiodidae: Cholevinae: Leptodirini) - Lakota, Ján; Hlaváč, Peter; Lohaj, Roman; Čeplík, Dávid (Zootaxa, 2014)
Reinholdina deelemanorum Giachino & Moravec, 2009 is a junior synonym of Parapropus neumanni Müller, 1911. The genus Reinholdina Giachino & Moravec, 2009 is placed in the synonymy with Parapropus Ganglbauer, 1899.